Pemeriksaan Status Gizi Indeks Massa Tubuh Menurut Umur untuk Deteksi Dini Status Gizi Tidak Normal pada Remaja Puteri - Atikah Rahayu (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
AbstractMacro and micro nutrient deficiency in female adolescents causes the body to be thin and weight (BB) to drop dramatically impact on nutritional status becomes abnormal. One risk factor is an unbalanced diet. The nutritional status of adolescent girls can be seen from the results of the examination of Body Mass Index (BMI / U) by age. The importance of this nutritional status check is carried out considering that adolescent girls are one of the most potential human resources to assist development in a country because adolescents are the next generation and determiners of the future of this nation, in addition, adolescent girls are prospective mothers who will give birth to children of high quality to use for the development of a nation if it consumes food based on balanced nutrition. The examination of abnormal nutritional status of 68 teenage girls (39.3%) can trigger educational institutions in collaboration with health institutions and parents to immediately conduct nutritional interventions in the form of nutritional education, or cooking demonstrations of balanced nutrition requirements for teenagers and parents as a program to tackle problems of abnormal nutritional status and the risk of anemia for adolescent girls, so that nutritional problems in adolescents can be quickly resolved.